The essentiality of digital transformation in activities of Vietnam trade union - Nguyễn Hải Hoàng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In order to contribute to improving the performance of trade unions and at the same time successfully implement the national digital transformation process, it is necessary to have digital transformation in the operation of Vietnam Trade Union as a necessity. This is the content that the author aims to clarify in this article.